2020
DOI: 10.51355/jstem.2020.93
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the STEM Fields in Education- and Career-Related Discussions between Finnish Parents and their Adolescent Children

Abstract: Occupational gender segregation in Finland is high and persistent in the fields of science, technology, engineering, and mathematics. Previous research has concluded that, rather than differences in aptitude, gendered educational and vocational choices originate from more complex system of attitudes, self-concepts, motivations and both direct and indirect social influences, all of which shape young people’s future goals. In the sphere of social influences on career choice, parents play a special role in adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Thus, female secondary school students valued, to a lesser extent than male students, three of the competences evaluated, highlighting among them the disciplinary STEM competences along with problem solving and metacognitive skills. The gender gap in STEM fields has raised concern in the scientific community [8][9][10][11], where different factors have been identified as generating this inequality [8,10]. In this case, however, contrary to the initial hypotheses, the use of project-based learning methodologies did not make it possible to reduce the differences between boys and girls in secondary schools, even though this strategy has been suggested to favor women's vocational interest in STEM careers and professions [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, female secondary school students valued, to a lesser extent than male students, three of the competences evaluated, highlighting among them the disciplinary STEM competences along with problem solving and metacognitive skills. The gender gap in STEM fields has raised concern in the scientific community [8][9][10][11], where different factors have been identified as generating this inequality [8,10]. In this case, however, contrary to the initial hypotheses, the use of project-based learning methodologies did not make it possible to reduce the differences between boys and girls in secondary schools, even though this strategy has been suggested to favor women's vocational interest in STEM careers and professions [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, STEM subjects have dense syllabuses that are difficult to assimilate when they are taught in a generic way, using traditional methodologies to impart the basic foundations compared to more innovative methodologies from the didactic point of view [6,7]. On the other hand, studies have found a clear gender gap, with women underrepresented in university careers linked to STEM, which already manifests itself early on [5,[8][9][10][11]. Notwithstanding, it has been shown that a high percentage of pre-university students considered men and women as equally good professionals in STEM jobs [12].…”
Section: Stem Learning In Secondary Schoolmentioning
confidence: 99%